Role of Phytohormones in Piriformospora indica-Induced Growth Promotion and Stress Tolerance in Plants: More Questions Than Answers - Xu, Le; Wu, Chu; Oelmüller, Ralf; Zhang, Wenying (Frontiers in Microbiology, 2018)
Phytohormones play vital roles in the growth and development of plants as well as in interactions of plants with microbes such as endophytic fungi. The endophytic root-colonizing fungus Piriformospora indica promotes plant growth and performance, increases resistance of colonized plants to pathogens, insects and abiotic stress. Here, we discuss the roles of the phytohormones (auxins, cytokinin, gibberellins, abscisic acid, ethylene, salicylic acid, jasmonates and brassinosteroids) in the interaction of P. indica with higher plant species, and compare available data with those from other (beneficial) microorganisms interacting with roots. Furthermore, phytohormones play crucial roles in systemic signal propagation as well as interplant communication. P. indica interferes with plant hormone synthesis and signalling to stimulate growth, flowering time, differentiation and local and systemic immune responses. Plants adjust their hormone levels in the roots in response to the microbes to control colonization and fungal propagation. The available information on the roles of phytohormones in beneficial root-microbe interactions opens new questions of how P. indica manipulates the plant hormone metabolism to promote the benefits for both partners in the symbiosis.